2018
DOI: 10.1097/ta.0000000000001880
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid in severe trauma patients managed in a mature trauma care system

Abstract: Therapeutic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…[ 3 , 4 ] Survival is achieved via a complex set of metabolic, endocrine, and immunological pathways that mobilize fuel sources and minimize blood loss, so that our vital organs may continue to be perfused and function. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 , 4 ] Survival is achieved via a complex set of metabolic, endocrine, and immunological pathways that mobilize fuel sources and minimize blood loss, so that our vital organs may continue to be perfused and function. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Rats subjected to severe trauma develop an elevation over time in d-dimers, tPA, and plasmin activity [11], with a subsequent fall in clot strength (12). The activation of fibrinolysis and the loss of clot strength suggest mechanisms that would explain why anti-fibrinolytic drugs have demonstrated benefit in the treatment of trauma [1316].…”
Section: Introductionmentioning
confidence: 99%
“…Testing currently includes viscoelastic tests such as rotational thromboelastometry or thromboelastography, thrombin generation tests, and clot waveform analysis, all of which help identify an abnormality in the clotting cascade. 50 One study found that thromboelastography-guided resuscitation during mass transfusion, as compared with conventional coagulation assay guidance, improved survival and required fewer plasma and platelet transfusions during the early phase of resuscitation. 42 Although more research is needed to support their use, these viscoelastic tests, referred to as viscoelastic monitoring, can guide correction of coagulopathy with specific blood product components or coagulation factor concentrates.…”
Section: Laboratory Testingmentioning
confidence: 99%